The Relationship Of Sports Clubs “Open Spaces”To Representations Of Citizenship Values "Vietnamese Sports Clubs Open As A Model" - بتقة ليلى (sports creativity, 2025)
This study aims to highlight the role of sports clubs in promoting and consolidating the values of citizenship, as an institution of socialization, through the Vietnamese experience with open sports arenas as sports clubs prepared by the state for the residents of those neighborhoods, and this is through an occasional sample of the visitors of these squares in the areas of vung tau and Saigon. In light of the spread of the culture of practicing sports as a healthy lifestyle that helps individuals adapt to themselves and with others, through this research paper we want to know the role of sports clubs as a secondary social institution in establishing and strengthening the values of citizenship in the hearts of individuals - as a matter of social interaction with the external environment - and this By the following indications:1- Identity recognition/2- Self-construction/3- Behavior modification